Influence of Process Energy on the Formation of Imperfections in Body-Centered Cubic Cells with Struts in the Vertical Orientation Produced by Laser Powder Bed Fusion from the Magnesium Alloy WE43 - Jan Jaroš; Ondřej Vaverka; Sascha Senck; Daniel Koutný (Micromachines, 2024)
The low specific density and good strength-to-weight ratio make magnesium alloys a promising material for lightweight applications. The combination of the properties of magnesium alloys and Additive Manufacturing by the Laser Powder Bed Fusion (LPBF) process enables the production of complex geometries such as lattice or bionic structures. Magnesium structures are intended to drastically reduce the weight of components and enable a reduction in fuel consumption, particularly in the aerospace and automotive industries. However, the LPBF processing of magnesium structures is a challenge. In order to produce high-quality structures, the process parameters must be developed in such a way that imperfections such as porosity, high surface roughness and dimensional inaccuracy are suppressed. In this study, the contour scanning strategy is used to produce vertical and inclined struts with diameters ranging from 0.5 to 3 mm. The combination of process parameters such as laser power, laser speed and overlap depend on the inclination and diameter of the strut. The process parameters with an area energy of 1.15–1.46 J/mm2 for struts with a diameter of 0.5 mm and an area energy of 1.62–3.69 J/mm2 for diameters of 1, 2 and 3 mm achieve a relative material density of 99.2 to 99.6%, measured on the metallographic sections. The results are verified by CT analyses of BCCZ cells, which achieve a relative material density of over 99.3%. The influence of the process parameters on the quality of struts is described and discussed.